Kikuchi-Fujimoto disease - Adhikari, RC (Journal of Pathology of Nepal, 2012)
Kikuchi-Fujimoto disease or histiocytic necrotizing lymphadenitis is a benign, self limited condition with higher prevalence among Japanese and other Asiatic people. Though the cause of this disease remains unclear, viral cause has been suggested. It is clinically characterized by lymphadenopathy, fever, cutaneous erythema, diarrhea, vomiting, sore throat, arthralgia, myalgia and hepatosplenomegaly. Laboratory findings are non-specific and Kikuchi-Fujimoto disease is generally diagnosed based on characteristic histopathological findings. Affected lymph nodes demonstrate paracortical areas of apoptotic necrosis with abundant karyorrhectic debris, proliferation of histiocytes, plasmacytoid monocytes, small and transformed lymphocytes in the absence of neutrophils. Kikuchi-Fujimoto disease is thought to have three evolving phases: proliferative, necrotizing and xanthomatous. Fine needle aspiration smears from involved lymph nodes reveal characteristic intra- and extracellular apoptotic nuclear debris with admixed crescentic macrophages on a reactive lymphoid background. Differential diagnoses of this disease are lymphoma, systemic lupus erythematosus, toxoplasmosis, tuberculosis, myeloid tumor and even metastatic adenocarcinoma. Treatment is symptomatic and spontaneous recovery occurs in 1 to 4 months. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6028 JPN 2012; 2(3): 226-230